Utilización de materiales ferromagnéticos y NaCl para el mejoramiento de la distribución de la SAR en hipertermia oncológica - Vera Hernández, A; Leija Salas, L; Sido, M. N.; Marchal, C.; Hernández Mier, Y (Revista Mexicana de Ingenieria Biomedica, 2002)
Hyperthermia is one of the therapies used against cancer, however, it is necessary to improve this technique to avoid healthy tissue damage due to the temperature rising. This work presents different alternatives to achieve a local electromagnetic hyperthermia. Results of using different materials to increase local heating are shown. This material can be introduced inside tumors, o near them, to take advantage of magnetic and electric fields. The materials tested were: sodium chloride, ferrite, and ferrofluids. The measurements were performed inside a TX150 phantom and using the unique impulse technique.